Research and Development of Microphysiological Systems in Japan Supported by the AMED-MPS Project - Ishida, Seiichi (Frontiers in Toxicology, 2021)
Microphysiological systems (MPS) have been actively developed as a new technology for in vitro toxicity testing platforms in recent years. MPS are culture techniques for the reconstruction of the specific functions of human organs or tissues in a limited space to create miniaturized human test systems. MPS have great promise as next-generation in vitro toxicity assessment systems. Here, I will review the current status of MPS and discuss the requirements that must be met in order for MPS to be implemented in the field of drug discovery, presenting the example of an in vitro cell assay system for drug-induced liver injury, which is the research subject in our laboratory. Projects aimed at the development of MPS were implemented early in Europe and the United States, and the AMED-MPS project was launched in Japan in 2017. The AMED-MPS project involves industry, government, and academia. Researchers in the field of drug discovery in the pharmaceutical industry also participate in the project. Based on the discussions made in the project, I will introduce the requirements that need to be met by liver-MPS as in vitro toxicity test platforms.